Regional patterns of δ13C and δ15N for European common cuttlefish (Sepia officinalis) throughout the Northeast Atlantic Ocean and Mediterranean Sea. Issue 9 (1st September 2021) - David Wells, R. J.; Rooker, Jay R.; Addis, Piero; Arrizabalaga, Haritz; Baptista, Miguel; Bearzi, Giovanni; Fraile, Igaratza; Lacoue-Labarthe, Thomas; Meese, Emily N.; Megalofonou, Persefoni; Rosa, Rui; Sobrino, Ignacio; et al.
Abstract : Stable isotope compositions of carbon and nitrogen (expressed as δ 13 C and δ 15 N) from the European common cuttlefish ( Sepia officinalis ) were measured in order to evaluate the utility of using these natural tracers throughout the Northeast Atlantic Ocean and Mediterranean Sea (NEAO-MS). Mantle tissue was obtained from S. officinalis collected from 11 sampling locations spanning a wide geographical coverage in the NEAO-MS. Significant differences of both δ 13 C and δ 15 N values were found among S. officinalis samples relative to sampling location. δ 13 C values did not show any discernable spatial trends; however, a distinct pattern of lower δ 15 N values in the Mediterranean Sea relative to the NEAO existed. Mean δ 15 N values of S. officinalis in the Mediterranean Sea averaged 2.5‰ lower than conspecifics collected in the NEAO and showed a decreasing eastward trend within the Mediterranean Sea with the lowest values in the most eastern sampling locations. Results suggest δ 15 N may serve as a useful natural tracer for studies on the population structure of S. officinalis as well as other marine organisms throughout the NEAO-MS.